Non‐thymoma‐associated exfoliative dermatitis in a European shorthair cat: A case report - Marcin Szczepanik (Wiley, 2021)
Abstract The current case report presents a case of non‐thymoma‐associated exfoliative dermatitis in an 8‐year‐old European Shorthair female cat. The animal displayed extensive alopecia and excessive peeling of the epidermis. There were no other apparent disorders, except for the skin lesions. Roentgenographic and sonographic examinations, complete blood count and blood serum chemistry analyses, and skin biopsy were performed. The histopathological investigation revealed hyperkeratosis of the epidermis and the infiltration of lymphocytes and macrophages at the dermal‐epidermal junction around the hair follicles and sebaceous glands. Moreover, edema of the basal layer and melanin migration from the epidermis to the dermis were observed. The patient underwent treatment with immunosuppressive doses of prednisolone, antibiotic therapy, and baths in anti‐seborrheic shampoos and displayed resolution. However, recurrence was observed after one month. Consequently, the patient received cyclosporine A, in addition to the aforementioned treatment and the lesions resolved without relapse.